"Stealing the fire": language as theme and strategy in South African women's poetry. (3rd May 2016) - Byrne, Deirdre
ABSTRACT: The twenty-first century has seen a dramatic increase in the amount of poetry being written and published by South African women writers. Unfortunately, this has not been matched by a corresponding increase in critical responses. This article attempts to address this situation through a discussion of the linguistic themes and strategies found in South African women's poetry, seen within the artistic and socio-political context of post-apartheid South Africa. Nevertheless, South African women poets use poetry as a vehicle for defining identities within the contested postcolonial space. They also write in protest against their silencing by patriarchy and by colonial forces. They frequently use language to overcome the gendered binary opposition between private and public utterance. Finally, women poets engage productively with cultural, ethnic and gender difference. While it is not possible exhaustively to define the ways in which South African women poets use language, the article identifies significant trends and concerns in this area.